The use of DryShield versus rubber dam isolation systems among pediatric patients with different airway patency: A randomized clinical trial - Sara M. Bagher; Ghalia Y. Bhadila; Njood H. Alqahtani; Njood H. Alharbi; Osama M. Felemban (Elsevier, 2024)
Objectives: This randomized clinical trial aimed to evaluate the impact of DryShield isolation (DSI) and rubber dam isolation (RDI) system usage on vital signs, behavior, pain and discomfort, and chairside time required among children with different airway patencies based on the Modified Mallampati Classification (MMC). Material and methods: Healthy, cooperative children who required fissure sealant in at least two contralateral, fully erupted, permanent first molars were included. Airway patency was determined by two trained and calibrated dentists using the MMC. The participants were categorized based on their MMC scores into patent airways (classes I and II) and non-patent airways (classes III and IV). The dental procedure was videotaped during treatment, and vital signs, including arterial oxygen saturation, heart rate, and blood pressure, were recorded every 3 min. The participants' subjective pain and discomfort were evaluated using a previously validated Arabic interview questionnaire and a validated Arabic version of the Wong-Baker Faces Pain Rating Scale. The participants' behavior and behavioral pain were evaluated utilizing the Frankl Behavior Scale and the face, legs, activity, cry, and consolability scales, respectively. Results: There were no significant differences in any of the vital signs between DSI and RDI. DSI use yielded a significant reduction in chairside time (P < 0.001) and was more bothersome (P < 0.001) than RDI use among all participants, regardless of airway patency. DSI was associated with significantly better behavior during the dental procedure (P = 0.002) and less behavioral pain (P < 0.001) among all participants, regardless of airway patency. Conclusion: Irrespective of airway patency, DSI outperformed RDI in terms of behavior, pain, and procedure duration; however, DSI was characterized by noise, pressure on soft tissues, and an increased tendency to induce gag reflexes.